Investigation of the pharmacological effect and mechanism of mountain-cultivated ginseng and garden ginseng in cardiovascular diseases based on network pharmacology and zebrafish experiments - Ting Yu; Yan-Xin Zhang; Xin-Juan Liu; Dan-Qing Chen; Dan-Dan Wang; Guo-Qin Zhu; Guo-Qin Zhu; Qi Gao; Qi Gao (Frontiers Media S.A., 2022)
Ginseng (Panax ginseng C.A. Mey) is a kind of perennial herb of the Panax genus in the Araliaceae family. The secondary metabolites of mountain-cultivated ginseng (MCG) and garden ginseng (GG) vary greatly due to their different growth environments. To date, the differences in their pharmacological effects on cardiovascular diseases (CVDs) and their clinical applications remain unclear. To distinguish between the components of MCG and GG, ultra-high-performance liquid chromatography-quadrupole time-of-flight tandem mass spectrometry (UPLC-Q-TOF/MS) was performed. Next, the relationship between the expression of metabolites and the categories of the sample were analyzed using supervised partial least squares discriminant analysis and orthogonal partial least squares discriminant analysis. A network-based pharmacology approach was developed and applied to determine the underlying mechanism of different metabolites in CVD. In the present study, the role of MCG and GG in angiogenesis and their protective effects on damaged blood vessels in a vascular injury model of zebrafish were investigated. Using UPLC-Q-TOF/MS, 11 different metabolites between MCG and GG were identified. In addition, 149 common target genes associated with the metabolites and CVD were obtained; these targets were related to tumor protein P53, proto-oncogene tyrosine-protein kinase Src, human ubiquitin-52 amino acid fusion protein, ubiquitin-40S ribosomal protein S27a, polyubiquitin B, signal transducer and activator of transcription 3, isocitrate dehydrogenase 1, vascular endothelial growth factor A, glycose synthase kinase-3B, and coagulation factor II and were associated with the regulation of the phosphoinositide 3-kinase-Akt signaling pathway, the tumor necrosis factor signaling pathway, and the hypoxia-inducible factor-1 (HIF-1) signaling pathway, which play important roles in the curative effect in CVD treatment. Both types of ginseng can promote the growth of the subintestinal vessel plexus and protect injured intersegmental vessels through the HIF-1α/vascular endothelial growth factor signaling pathway in a dose-dependent manner. In addition, MCG has a stronger impact than GG. This is the first time metabolomics and network pharmacology methods were combined to study the difference between MCG and GG on CVDs, which provides a significant theoretical basis for the clinical treatment of CVD with two kinds of ginseng.